Privatization Policy and Public Service Delivery in Nigeria - Ugo Chuks Okolie; Idongesit David Udom (Universitas Pendidikan Indonesia, 2023)
Nigeria has gone through different phases in the shrinking of her public service through various forms of privatization of public enterprises. The efficiency of these privatized enterprises since the policy commenced is still left in doubts due to major failures and sometimes, the extinction of some of these organizations. Against this backdrop, this study examines the impact of the concession model of privatization policy on the public service delivery in Nigeria. This paper adopted the analytical method and relies on secondary data and utilizes the content analysis for interpretation of data collected. The paper relied on the public choice theory to posit that the main purpose of government as a service agency is to extend to the people certain essential services on a fair and equitable basis without delay. The paper therefore concludes that Concession model of privatization policy remains a major key to significant improvement in the public service delivery in Nigeria.